RETRACTED: Perkembangan dan Kontroversi Mengenai Eksistensi Multiverse - Romli, Sunaryo; Muslim, Muslim; Suhandi, Andi (PSEJ (Pancasakti Science Education Journal), 2023)
RETRACTED After careful consideration and thorough review of the article published in the PSEJ (Pancasakti Science Education Journal) entitled "Perkembangan dan Kontroversi Mengenai Eksistensi Multiverse", Vol. 8 No. 1, pp. 15-22, April 2023, DOI: https://doi.org/10.24905/psej.v8i1.161, this article has been withdrawn from the PSEJ (Pancasakti Science Education Journal) due to discrepancies with the journal's publication guidelines. The similarity check conducted by the editorial team before publication fell below the minimum threshold required by the journal. However, this article contains content that, after careful review, indicates a similarity to an article published by Frederick Ray Popo at https://lsfcogito.org/multiverse-menembus-batas-pengetahuan/ The document and its contents have been removed from the PSEJ (Pancasakti Science Education Journal), and reasonable efforts will be made to remove all references to this article.